Cortical signature of patients with HBV-related cirrhosis without overt hepatic encephalopathy: a morphometric analysis - Wu, Xiu; Lv, Xiao-Fei; Zhang, Yu-Ling; Wu, Hua-Wang; Cai, Pei-Qiang; Qiu, Ying-Wei; Zhang, Xue-Lin; Jiang, Gui-Hua (Frontiers in Neuroanatomy, 2015)
Previous studies have shown that patients with hepatitis B virus-related cirrhosis (HBV-RC) without overt hepatic encephalopathy (OHE) are associated with a varying degree of cognitive dysfunction. Several resting-state functional magnetic resonance imaging (fMRI) studies have been conducted to explore the neural correlates of such cognitive deficits, whereas little effort has been made to investigate the cortical integrity in cirrhotic patients without OHE. Here, using cortical thickness, surface area and local gyrification index (lGI), this study performed a comprehensive analysis on the cortical morphometry of patients with HBV-RC without OHE (HBV-RC-NOHE) versus matched healthy controls. Compared with healthy controls, we found significantly increased cortical thickness in the bilateral lingual and parahippocampal gyrus, right posterior cingulate cortex, precuneus, peri-calcarine sulcus and fusiform gyrus in patient with HBV-RC-NOHE, which may closely relate to be the low-grade brain edema. Cortical gyrification analysis showed significantly increased lGI in the left superior and inferior parietal cortex as well as lateral occipital cortex, which was speculated to be associated with disruptions in white matter connectivity and sub-optimal intra-cortical organization. In addition, the mean cortical thickness/lGI of the regions with structural abnormalities was shown to be negatively correlated with psychometric hepatic encephalopathy score (PHES) of the patients with HBV-RC-NOHE. These morphological changes may serve as potential markers for the preclinical diagnosis and progression of HBV-RC-NOHE.